2008
DOI: 10.1080/0972060x.2008.10643605
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial Activity ofSatureja parvifolia(Phil.) Epling Essential Oil

Abstract: Chemical composition, GC and GC-MS analysis and in vitro antibacterial activity of the essential oils of the aerial parts of Satureja parvifolia (Phil.) Epling collected in San Juan Province Argentine were performed. Twenty six compounds were identified accounting for 94.1% (area %) of the essential oil. The major constituents were piperitone (34.9%), piperitenone (27.3%), cis-piperitenone epoxide (15.0%) and piperitenone oxide (6.0%). The in vitro antimicrobial activity of the essential oil was investigated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…According to the reports presented in Table 3, some Satureja species have unusual chemical profiles. For example; piperitone, piperitenone, and piperitenone oxide are the main compounds of S. parvifolia and S. fruticosa Beguinot (Cabana et al, 2013;Coelho et al, 2007Coelho et al, , 2012Dambolena et al, 2009;Lima et al, 2011;Luna et al, 2008;Viturro et al, 2000). Additionally, camphor was determined as the major compound of S. visianii Silic (Bezic et al, 2009;Dunkic & Bezic, 2008;Vidic et al, 2009).…”
Section: Volatiles (Terpenes)mentioning
confidence: 99%
“…According to the reports presented in Table 3, some Satureja species have unusual chemical profiles. For example; piperitone, piperitenone, and piperitenone oxide are the main compounds of S. parvifolia and S. fruticosa Beguinot (Cabana et al, 2013;Coelho et al, 2007Coelho et al, , 2012Dambolena et al, 2009;Lima et al, 2011;Luna et al, 2008;Viturro et al, 2000). Additionally, camphor was determined as the major compound of S. visianii Silic (Bezic et al, 2009;Dunkic & Bezic, 2008;Vidic et al, 2009).…”
Section: Volatiles (Terpenes)mentioning
confidence: 99%
“…The major components were piperitone (34.9%), piperitenone (27.3%), cis-piperitenone epoxide (15.0%), and piperitenone oxide (6.0%) [11]. Zygadlo et al [14] reported piperitenone oxide (69.8%), piperitenone (5.6%), and pulegone (4.4%) as the main constituents of S. parvifolia EO collected from Central Argentina.…”
mentioning
confidence: 98%
“…Eugenol has also shown synergistic effects with conventional antimicrobials [29]. Documented investigations have demonstrated antibacterial activities of EOs rich in piperitenone oxide and piperitone (major constituents of the P. epithilicus and S. robusta oils obtained in the present work) [30]. The presence of these compounds may account for the recorded activities.…”
Section: Antibacterial Activities Of Essential Oilsmentioning
confidence: 56%